Analytical Solution of UCM Viscoelastic Liquid with Slip Condition and Heat Flux over Stretching Sheet: The Galerkin Approach. (25th February 2020) - Khan, Zeeshan; Rasheed, Haroon Ur; Noor, Sahib; Khan, Waris; Shah, Qayyum; Khan, Ilyas; Kadry, Seifedine; Nam, Yunyoung; Nisar, Kottakkaran Sooppy
Abstract : This paper provides a substantial amount of study related to coupled fluid flow and heat conduction of an upper-convected-Maxwell viscoelastic liquid over a stretching plane with slip velocity. A new model, presented by Christov, for thermal convection is employed. The partial differential equations are converted to ordinary differential equations by using appropriate transformation variables. The transformed equations are solved analytically by using the Galerkin method. For the sake of soundness, a comparison is done with a numerical method, and good agreement is found. The impacts of various parameters like slip coefficient, elasticity number, the thermal relaxation time of heat flow, and the Prandtl number over the temperature and velocity fields are studied. Furthermore, the Cattaneo–Christov heat flux model is compared with Fourier's law. Additionally, the present results are also verified by associating with the published work as a limiting case.